Competitive bout model as a tool for estimation of female karateka specific endurance - Alexandrova, A.; Penov, R.; Petrov, L.; Cholakov, K.; Kolimechkov, S. (European Journal of Physical Education and Sport Science, 2018)
The aim of this study was to establish the functional state of female karate practitioners during a Shotokan kumite competition by measuring changes in their lactate concentration and also by designing a training exercise model, that matches the workload during competitions. Seven female karate practitioners, between the ages of 18 and 30, took part in this research, which was conducted in two stages: 1) in competitive conditions during the National Shotokan Karate Championship, where capillary blood lactate concentration was measured both after the warm-up and after each bout; 2) in training conditions, where again the blood lactate concentration was determined post warm-up and after performance of the karate kumite model, which consisted of a series of techniques designed to simulate competitive kumite, and in addition to this the heart rate was recorded continuously using a heart-rate telemetry system. According to the results from the maximal aerobic test, the training level of the female karatekas tested was comparable to that of internationally ranked competitors from other countries. The lactate concentrations measured during the competition were a more reliable predictor of the competitive ranking in comparison to VO2max. The designed karate kumite training model simulated well the level of competitive load based on a comparison of the measured lactate concentrations and those determined during the competition. In all the women tested, the heart rate measured after the simulated kumite was close to the maximal values (about 180 bpm), and thus did not adequately reflect the work intensity. In conclusion, since lactate concentration accurately reflects competitive output, and correlates with the exercise intensity during a designed training model, it could be used for evaluation of the physical load and specific endurance, particularly of female karate practitioners.